Connaissance de Dieu: Présence intentionnelle ou réelle? - Bourassa, François (Gregorianum, 1987)
Reflecting on the mystery of the divine life in us through faith and charity, the theologians of the great Medieval period have perceived this mysterious presence as formally constituted by the knowledge and love of God, in accordance with the revealed doctrine of God's image in man (DS 3815). This necessarily implied on the part of theological reflection a theory of knowledge which in its broad lines found its definite expression in the analyses of St Thomas. However, according to a widespread thesis of commentators, knowledge would consist in becoming or being something other than oneself, through the "merely intentional" presence and union of the object known to the knowing subject. Knowledge is not by itself real union because intentional being, since it is not being in self and for self, differs from existing being. Or else, this "intentional" knowledge is said to characterise all created knowledge, even the beatific vision, while it cannot be found in God; this no longer corresponds to St Thomas' way of speaking. Hence the various opinions and discussions as to the reality of the divine presence and how the intentional character of the knowledge and love of God needs to be understood. Therefore, the first point to be studied is the knowledge of God. With this question in mind, the first part of the article attempts first to sum up the main conclusions of many studies on the nature of knowledge in S. Thomas' work; however, it does this only in view of determining by analogy what according to St Thomas constitutes the unique character of God's knowledge: that which God has of himself, in the eternal contemplation of his Word in whom rests all his Love; that also which he grants to man through the communication of his Word, already in the illumination of faith, prelude to the vision of God's essence when "we shall see him as he is" and as "he knows himself". The second part of the article attempts to trace back the corresponding notion of "intentional", while taking into account the variations which it has undergone later.